Digitizing the church - challenges for academic theology - Karcher, Stefan (Interdisciplinary forum of digital textual sciences, 2018)
(Den Beitrag auf Deutsch weiterlesen) “Digital church” (#DigitaleKirche ) is currently much discussed. It’s inspiring (and sometimes amusing) to follow the debates about digital tools, social media…